Industry 4.0: Future Industries of Thailand - Kumpirarusk, Panuwong; Rohitratana, Kaewta (WMS Journal of Management, 2018)
Industry 4.0 is the challenging and flagship policy to restructure the industrial sector of Thailand from labor intensive and basic technology in producing non-sophisticated and low value-added products and services to the industries driven by knowledge and advanced technologies, creativity and development as well as innovation in producing sophisticated and high value-added products and services. Industry 4.0 will result in higher income and higher economic growth that can make Thailand overcome the middle income trap. The research objective is to study and compare opportunities and potential of 10 target industries and to select the most highly potential 3 target industries. This qualitative research is based on analysis of secondary data and conduct of focus groups to collect additional primary data. Three highly potential industries include food for the future, biotechnology, as well as parts and spare parts, maintenance, repair and overhaul for aerospace. All of them can be regarded as future industries of Thailand.